Upaya Meningkatkan Hasil Belajar Matematika dengan Pendekatan Contextual Teaching and Learning (CTL) pada Siswa Kelas V - Nurhayati, Sri (TSAQOFAH, 2021)
The purpose of this study was to determine the improvement of student learning outcomes on the subject of integer arithmetic operations with the CTL. approach. The location of the research was carried out at SD Negeri 2 Mantang, Batukliang District, Central Lombok Regency. The subjects of this study were fifth grade students of SD Negeri 2 Mantang, fifth grade teachers of SD Negeri 2 Mantang and observers. The research is divided into 2 cycles, each cycle consists of planning, implementation, observation and reflection stages. While the indicators of the success of this classroom action research are achieved if students have a minimum grade point average of 6.5 and complete class learning above 75%. In the first cycle, the students achieved a minimum grade point average of 69 while the mastery of learning was 65%. Cycle II achieved an average grade of 84 and the learning completeness was 85%. Based on the student learning outcomes above, it can be concluded that learning with the CTL approach can improve the learning outcomes of fifth grade students at SD Negeri 2 Mantang, Batukliang District, Central Lombok Regency, on the subject of integer arithmetic operations, so it is recommended that in teaching the subject of integer arithmetic operations, teachers should use the CTL approach.